PENGARUH MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN BUSANA GENERASI Z - Nanda Lidya Fatimah; Nadhifa Zulfa Aulia; Ghina Anjar Firossa; Adhi Kusumastuti; Sita Nurmasitah (Universitas Negeri Jakarta, 2026)
Abstract. This study examines the influence of social media on Generation Z's clothing purchasing decisions in Indonesia, a generation known as digital natives who are highly exposed to fashion trends through platforms such as TikTok and Instagram. The research respondents are 109 Gen Z individuals who are active on social media and have experience buying or considering buying clothing through these platforms. Their consumption patterns tend to be influenced by visual content, influencers, and user reviews, often leading to purchases that are not based on actual needs. This study aims to analyse the extent to which social media influences Gen Z's clothing purchasing decisions by reviewing indicators such as visual appeal, influencer exposure, advertisements, and the tendency to buy after seeing reviews. The research method used a quantitative approach through a survey, with Likert scale variable measurements. The results show that TikTok is the dominant platform, while visual appeal and influencers are the most influential indicators, and advertisements have the lowest impact. In terms of purchasing decisions, user reviews are the strongest factor. Regression analysis confirmed that social media has a significant impact on Gen Z consumers' purchasing decisions (β = 0.74; p < 0.001; R² = 0.41). These findings confirm the strong role of organic content in shaping the fashion consumption behaviour of the younger generation.